Worker participation in the new South Africa - Moore, Kurt Gavin (Centre for Law and Society, 2024)
The economies of Third World countries, almost without exception, are plagued by problems such as high inflation and mass unemployment, resulting in widespread poverty and an inevitable economic downward spiral. Within this context, the immediate task of any new post-independence government, is to stabilise the economy and attract foreign investment. Set in a global economy, with industries that cannot compete on world markets, these countries resort to exploiting the only viable commodity they have, which is cheap labour. The new South African Government faces similar problems to the rest of the Third World, including large-scale illiteracy and a largely unskilled workforce. Fortunately, South Africa has opted for a different route to solve these problems. The ANC-led Government of National Unity has formulated a Reconstruction and Development Program (RDP) designed to meet the specific needs of South Africa. This plan is perceived by the millions of disadvantaged South Africans as being the solution to many of their problems. It would be naive to think that the RDP could succeed without finance. Minister without Portfolio, Mr Jay Naidoo, sums up the Government's sentiments as follows: "We are very conscious that unless we maintain fiscal discipline, the medium to long terms sustainability of the RDP will be at risk."1 This raises the question whether finance is the only key to the success of the RDP. The answer is to be found in the 'ANC's draft. of the RDP itself: "The success of the RDP does not only require finance. It also requires labour, skills and co-ordinated effort in combination with that finance."2 One of the basic principles of the RDP is the democratisation of South Africa. The RDP is more than just a policy document, it is an attempt, to extend democracy beyond the ballot box. Having finally attained political democracy for all South Africans, and in keeping with the RDP, the next step is to work towards industrial democracy. This means giving the workers a say in their daily working lives. This is by no means a new topic, in South Africa it has been debated in academic circles, on the shop floor and in boardrooms. However, the RDP adds new impetis to this topic. The focus of this paper is the immediate future of South African Labour Relations, specifically worker participation in the context of the RDP. The New Labour Relations Act [Act 66 of 1995] was passed in November 1995 which will bring about many changes to the current labour dispensation, this paper sets out to evaluate the New Labour Relations Act in the light of its proposals to extend industrial democracy and its impact on the development of industrial relations in South Africa. The paper will examine various models of worker participation, including the current dispensation (as of 1 January 1996) and ultimately attempts to assess their applicability to South Africa. Consideration will be given to the concept of extending the existing collective bargaining system as opposed to importing foreign systems of worker participation.